Assessing the Effects of Ginger Extract on Polyphenol Profiles and the Subsequent Impact on the Fecal Microbiota by Simulating Digestion and Fermentation In Vitro - Wang, Jing (Nutrients, 2020)
The beneficial effects of ginger polyphenols have been extensively reported. However, their metabolic characteristics and health effects on gut microbiota are poor understood. The purpose of this study was to investigate the digestion stability of ginger polyphenols and their prebiotic effects on gut microbiota by simulating digestion and fermentation in vitro. Following simulated digestion in vitro, 85% of the polyphenols were still detectable, and the main polyphenol constituents identified in ginger extract are 6-, 8-, and 10-gingerols and 6-shogaol in the digestive fluids. After batch fermentation, the changes in microbial populations were measured by 16S rRNA gene Illumina MiSeq sequencing. In mixed-culture fermentation with fecal inoculate, digested ginger extract (GE) significantly modulated the fecal microbiota structure and promoted the growth of some beneficial bacterial populations, such as Bifidobacterium and Enterococcus. Furthermore, incubation with GE could elevate the levels of short-chain fatty acids (SCFAs) accompanied by a decrease in the pH value. Additionally, the quantitative PCR results showed that 6-gingerol (6G), as the main polyphenol in GE, increased the abundance of Bifidobacterium significantly. Therefore, 6G is expected to be a potential prebiotic that improves human health by promoting gut health.